Validity of serum galectin-4(Gal-4) in diagnosis of gastric adenocarcinoma: - Al-Derzi, Aida R.; Al-Ammiri, Hind H.; Ghanim, Nahla (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Galectin-4 is one of a b-galactosides binding proteins family that recognize a variety of glycan -containing proteins at the cell surface and are overexpressed in various tumors, including gastric cancer. Galectin-4 overexpression as well as changes in their subcellular distribution has been associated with gastric cancer progression and poor prognosis. It may provide diagnostic molecular markers for gastric cancer as well as clues for developing therapeutic targets on individual basis.Objectives : The aims of the present study were to determine the levels of GAL-4in the sera of healthy people and patients with gastric cancer and also, to investigate the validity of using GAL-4 as a specific diagnostic marker of gastric cancer.Patients and methods: twenty five gastric cancer patients were included in this study. They were among patients who attending the Endoscopy Department in Baghdad Medical City Teaching Hospital, during the period from December 2011 to July 2012. In addition, fifteen apparently healthy person were chosen as a healthy control group. For these two groups, serum level of GAL-4 using sandwich ELISA technique was carried out.Results: There was a statistically significant difference in serum level of GAL-4 among gastric adenocarcinoma patients in comparison to healthy controls (p≤0.001), using receiver operating characteristic curve (ROC) area, serum GAL-4 has high area under the curve (0.924) with a cut off value equal to or above 0.42ng/ml which was associated with the highest sensitivity (100%).Conclusions: The current study showed that serum levels of GAL-4 were significantly higher in patients with malignant gastric adenocarcinoma which may confirm a possible role of this marker in the pathogenesis of the disease, furthermore the highest sensitivity and best accuracy obtained from serum GAL-4 was by using a cut off values equal to or above 0.42ng/ml; Therefore, GAL-4 may be promising new diagnostic tools especially at early stages and among patients at high risk.